If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 = 6x + 2(-1x + 13) Reorder the terms: -10 = 6x + 2(13 + -1x) -10 = 6x + (13 * 2 + -1x * 2) -10 = 6x + (26 + -2x) Reorder the terms: -10 = 26 + 6x + -2x Combine like terms: 6x + -2x = 4x -10 = 26 + 4x Solving -10 = 26 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -10 + -4x = 26 + 4x + -4x Combine like terms: 4x + -4x = 0 -10 + -4x = 26 + 0 -10 + -4x = 26 Add '10' to each side of the equation. -10 + 10 + -4x = 26 + 10 Combine like terms: -10 + 10 = 0 0 + -4x = 26 + 10 -4x = 26 + 10 Combine like terms: 26 + 10 = 36 -4x = 36 Divide each side by '-4'. x = -9 Simplifying x = -9
| 4m^2+17m+15=0 | | 32y^5+4y^3=0 | | (3x^2-4x)(2x^3+3x-1)=0 | | 2x-2(7x-2)=64 | | -(x-7)=5+2(x-1) | | 18m+5=13m+5 | | 1.08(1.21)(8-x)=10 | | x^2+4-9=0 | | 18c+7=6c-77 | | a+5=-24 | | ln(2x+2)=2.5 | | 7x+4(4x-14)=59 | | 5b=4b-9 | | 110=5x+2(-7+10) | | 12(v+4)-4v=4(2v+4)-22 | | -p/3=4 | | 2sin^2x+sinx+1=0 | | b=4b-9 | | Y=1/2(x-4)^2-2 | | 4sin^2(x)=2cos(x) | | (cos(x)cot(x))/(1-sinx)=3 | | cosxcotx/1-sinx=3 | | 5x+15=-3x-11 | | x=5x^2+x*5 | | N+.6=n+.1+2n | | s^2+3s+8s+24= | | (1/6)^5 | | x^2+3x+24=47 | | 0=5x^2-24x+37 | | 4y+(y-1)=29 | | 4y-y+1=13 | | 5x^2+3x+24=47 |